Design and Simulation of Liftable Crawler Chassis for Combine Harvester - Bo, Jing; Lizhang, Xu (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Aiming at the needs of field operations in different deep mud, a liftable crawler chassis based on the connecting rod arm mechanism was designed, including the chassis upper frame, lifting mechanism, hydraulic cylinder, limit mechanism, left and right walking system. In the ADAMS software, a virtual prototype model of the lifting and lowering chassis is established. The angle variation of the frame on the chassis relative to the ground and the angular velocity and acceleration of each lifting rod were simulated and analyzed. These rules met the chassis lifting adjustment requirements during the harvester operation.